Direct monitoring of vesicular release and uptake in brain slices by multiphoton excitation of the styryl FM® 1-43. (March 2006) - Winterer, Jochen; Stanton, Patric K.; Müller, Wolfgang
Fluorescence imaging using FM® 1-43 and related styryl dyes has provided invaluable insights into presynaptic function of synapses in culture preparations, but has been limited in use for studying central synapses in vivo or in brain slices, because of excessive fluorescence background due to nonspecific membrane binding of dye. We demonstrate here that focal excitation of FM dyes using two-photon laser-scanning microscopy (TPLSM) provides high resolution of FM 1-43-labeled nerve terminals in brain slices by suppressing out-of-focus background and that a readily releasable pool of vesicles can be selectively and stably labeled by hypertonic shock despite slice diffusion barriers. We find direct TPLSM of FM 1-43-labeled nerve terminals to be superior to treatment of slices with either the fluorescent quencher sulforhodamine 101 or dye scavenger ADVASEP-7 in resolving nerve terminal against background fluorescence, enabling continuous monitoring of vesicular uptake, and release of styryl dyes from individual nerve terminals in brain slices.\